Towards a reliable bridge joint between REBCO coated conductors - Kirchner, A.; Nielsch, Kornelius; Huehne, R. (Journal of Physics: Conference Series, 2020)
REBa2Cu3O7-x (REBCO; RE = Y, Gd) coated conductor wires are commercially available up to a length of about 1 km. However, for large-scale devices like superconducting coils for high-field magnets several kilometres of a coated conductors are required. Therefore, it is desirable to use joints, which exhibit similar superconducting properties as the coated conductor itself. In this study, we jointed commercial REBCO coated conductors by a two-step procedure. At first, a superconducting soldering solution was developed and deposited on unstabilized coated conductors via chemical solution deposition. The soldering precursor is based on a Cu-rich solution with a metal cation ratio Y:Ba:Cu of 1:2:4. Secondly, a piece of the coated conductor was delaminated between the superconducting and the buffer layer and used as bridge between two other conductors covered with the soldering layer. Annealing the resulting bridge joint under pressure results in a mechanical stable configuration.
CRIS-Team Scopus Importer:2022-04-14